2020
DOI: 10.1016/j.pec.2019.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Humble doctors, healthy patients? Exploring the relationships between clinician humility and patient satisfaction, trust, and health status

Abstract: Objective: In medicine, numerous commentaries implore clinicians (e.g., physicians, physician assistants, nurse practitioners) to display more humility. However, given the complex power dynamics between patients and clinicians, one should not presume that patients desire and appreciate humble clinicians. This paper examines the relationship between clinician humility and patient outcomes, and aims to provide empirical evidence for the significance of clinician humility. Methods: In two studies, patients (N = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…When it comes to COVID-19, health behaviors may depend on various social and psychological factors (e.g., social contacts, Moussaoui et al, 2020;perceived control, Zheng et al, 2020). More generally, important medical decisions likely depend on other important factors such as patients' emotional state (e.g., Legg et al, 2015) and relationships between the patient and their care provider (e.g., Huynh et al, ,,2018Huynh & Dicke-Bohmann, 2020;Huynh & Sweeny, 2014). Future studies should examine whether intellectual humility can be engendered and employed to alter vaccine attitudes, intentions, and uptake.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…When it comes to COVID-19, health behaviors may depend on various social and psychological factors (e.g., social contacts, Moussaoui et al, 2020;perceived control, Zheng et al, 2020). More generally, important medical decisions likely depend on other important factors such as patients' emotional state (e.g., Legg et al, 2015) and relationships between the patient and their care provider (e.g., Huynh et al, ,,2018Huynh & Dicke-Bohmann, 2020;Huynh & Sweeny, 2014). Future studies should examine whether intellectual humility can be engendered and employed to alter vaccine attitudes, intentions, and uptake.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Public hospitals should ensure the quality and 'zero defect' services to their clients. So, patient satisfaction becomes the main indicator of a nation's health sector (Etier Jr, Orr, Antonetti, Thomas, & Theiss, 2016;Huynh & Dicke-Bohmann, 2020). It is essential, first of all, to understand what this study committed to analyzing the factors behind the reason for the patient shift from public to private hospitals in the study area.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The establishment of a relationship between service provider and a customer is particularly important in health care services, due to the relevance and complexity of health care services (Berry et al, 2008;Naidu, 2009;Chang et al, 2013;Huynh & Dicke-Bohmann, 2020). As patients lack skills to evaluate technical quality of health care services, according to Alrubaiee and Alkaa'ida (2011) they rely on interpersonal relations to infer quality judgments.…”
Section: The Specificity Of Health Care Servicesmentioning
confidence: 99%
“…the length of stay was shorter after a surgery in hospitals characterized with the highest level of patient satisfaction, as well as readmission rates and mortality rates. Patient satisfaction has been also reported to lead to patients' willingness to actively monitor their health care outcomes and patients' adherence to prescribed therapy and instructions of medical personnel, which have a positive influence on patients' recovery from illness (Sheppard et al, 2008;Dang et al, 2013;Martin et al, 2018;Materla et al, 2019;Huynh & Dicke-Bohmann, 2020;Ng & Luk, 2020). On the other hand, it has been shown that low levels of patient satisfaction adversely affect patients' physical, social, functional and overall quality of life (Drury et al, 2020).…”
Section: Introductionmentioning
confidence: 99%